Environmental, social, and governance performance: The role of Chinese employee stock ownership plans - Yasi Liu; Shaun McDowell; Chunxiao Xue; Jianing Zhang (Environmental Economics)
The challenges of global warming, resource depletion, and environmental protection require immediate action from corporations, governments, and communities globally. Implementing environmental, social, and governance (ESG) measures represents a key strategy for corporations in addressing sustainability concerns. This study investigates how the ESG performance of publicly listed companies in China is influenced by employee stock ownership plans (ESOPs). Utilizing a dataset covering 4,464 publicly listed Chinese corporations from 2009 to 2022, this analysis employs fixed-effects regressions to reveal the beneficial impact of ESOPs on corporate ESG ratings. A firm’s transition from non-ESOP to ESOP status raises ESG ratings by 1.213, representing 22% of the ESG score’s standard deviation. The findings indicate that greater involvement of the top management team in an ESOP weakens the positive impact of the ESOP on corporate ESG performance. The positive impact of ESOPs on ESG performance is insignificant in the agriculture sector but more pronounced in the manufacturing and service sectors, where the transition to ESOP status results in ESG score increases of 1.122 and 1.500, respectively. The issue of endogeneity is addressed by utilizing a lagged ESOP independent variable and applying two-stage least squares regression with the average ESOP serving as the instrumental variable. The findings confirm that causality runs from ESOP to ESG rather than ESG influencing ESOP. AcknowledgmentThis study was supported by the Department of Education of Zhejiang Province – General Program (Y202249981, Y202353438), the Wenzhou Association for Science and Technology – Service and Technology Innovation Program (jczc0254), the Wenzhou-Kean University Student Partnering with Faculty Research Program (WKUSPF202404, WKUSPF202411), the Wenzhou-Kean University International Collaborative Research Program (ICRP2023002, ICRP2023004), and the Wenzhou-Kean University Internal Research Support Program (IRSPG202205, IRSPG202206).